Nationalism On The Soccer: Between Naturalization Strategy And Public Pride - Barmuddin; Maudhy Satyadharma; Tina Trisarana Andriani Silondae (PT. Padang Tekno Corp, 2026)
This study is motivated by the growing debate over player naturalization in the Indonesian national soccer team, extending beyond performance to issues of nationalism and public pride. The controversy reflects tensions between pragmatic strategies for international success and symbolic expectations of national identity, shaped by media narratives, public opinion, and institutional decisions within Indonesia’s highly competitive and globalized soccer culture. The purpose of this research is to examine how media discourse constructs naturalization as both a strategic policy and a symbolic challenge to national identity. This study employs a qualitative research design using framing analysis based on Entman’s model and semiotic analysis grounded in Charles Sanders Peirce’s triadic theory. Data are collected from selected online media reports and public opinion surveys related to player naturalization in Indonesian soccer, which are analyzed to examine how nationalism and public pride are constructed and contested in media discourse.The findings reveal that media framing presents naturalization in dual narratives: as a pragmatic strategy to enhance team competitiveness and as a contested practice that may dilute national identity. Public support is largely shaped by expectations of improved performance, while opposition emphasizes symbolic nationalism and emotional attachment.